Peningkatan Kapasitas Simpang Sebidang Satu Arah dengan Simulasi Lalu Lintas Zero Point - Rompis, Semuel Y. R.; Kumaat, Meike (Jurnal Teknik, 2024)
The Zero Point intersection is the zero point of Manado City which is also the transfer point for public transportation passengers. The land use around this location is offices, pharmacies, shops, places of worship, hotels and there are also street vendors. This research is to analyze the characteristics of Zero Point intersections using the 2014 Indonesian Road Capacity Calculation (PKJI) method and the PTV Vissim application simulation to obtain alternative solutions.The results of the analysis are that the highest traffic volume (Q) occurred on Monday at 6493.4 cur/hour, vehicle capacity (C) was 2900 cur/hour, the degree of saturation (DJ) was 1,329, the intersection delay value (T) was 376,6 seconds/currency and the Level of Service (LOS) of the unsignaled intersection is at level D which indicates poor intersection performance.The results of this analysis then looked for alternative solutions by trial and error and the chosen alternative was to improve the performance of unsignalized intersections, namely the first was to change the vehicle's turning direction from the direction of Jl. Sudirman (next to Bank Sulut) which will turn towards Jl. Sam Ratulangi has to go around the Zero Point roundabout and the second alternative is to make changes, namely making a median or road divider on the Jl. Sudirman (next to Bank Sulut).